Implementasi Pembelajaran Diferensiasi di Madrasah Ibtidaiyah Raudhatut Taufiq - Anwar Anwar; Erwin Mahrus; Sukino Sukino (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2023)
Differentiation of learning is an old program in the world of education in Indonesia, but its application is still very new, so there are only a few schools that apply it. Madrasah Ibtidaiyah Raudhatut Taufiq Jl. Parit Jaya Sui Raya Kubu Raya, which has been implementing a differentiated learning system for one year. However, in its implementation, there are still some problems. In this study, the researchers aimed to find out how the implementation of differentiated learning for class teachers in grade 3 of Madrasah Ibtidaiyah Raudhatut Taufiq Jl. Parit Jaya Sui Raya Kubu Raya and what factors became obstacles to its implementation. Researchers use a qualitative approach. Data was collected through observation techniques, interviews and documentation. Based on this research, the results obtained were that the steps in implementing differentiated learning at Madrasah Ibtidaiyah Raudhatut Taufiq were taken through mapping, planning, and evaluation. The role of the head of Madrasah Ibtidaiyah Raudhatut Taufiq has also been quite good, which is marked by collaboration with parents, committees and the Ministry of Religion, support for learning resources, and provision of facilities and infrastructure. The main thing that becomes an obstacle to differentiated learning at Madarsah Ibtidaiyah Raudhatut Taufiq is the ability of teachers who are still minimal in understanding differentiated learning considering they still lack experience.